Correlation between Estimated Glomerular Filtration Rate (eGFR) and Sonographic Findings in Patients with Chronic Kidney Disease. - Neupane, NP; Lohani, B (Journal of Institute of Medicine Nepal, 2016)
Introduction: Ultrasound can also be used as a non-invasive modality for the evaluation and grading of the chronic kidney diseases. This study aims to correlate the various sonographic parameters with the various grades of CKD based on the eGFR.Methods: The study was a cross sectional study conducted over a period of one year. Study population was adult patients (between 20 to 60 years) with chronic renal disease not undergoing renal replacement therapy. Patients with liver disease and fatty changes in liver in ultrasound and patient with ascites were excluded from the study. Estimated glomerular filtration rate (eGFR) was calculated by using Cockcroft- Gault (CG) equation and CKD classified according to Kidney Disease Improving Global Outcomes (KDIGO) 2004. Ultrasound was performed for all patients and data were entered in a predesigned proforma. Data analysis was done using SPSS 21.0.Results: A total of 138 patients met the inclusion criteria and were included in the study. The mean renal length in our study was 9.03cm (±0.83) on right and 9.00cm (±0.82) on the left side. The mean renal cortical thickness of right kidney was 1.037±0.20 cm and of left kidney was 1.039-±0.20 cm. Renal length and renal cortical thickness demonstrated a negative correlation with grade of CKD while renal echogenicity grading demonstrated a positive correlation with CKD grade.Conclusions: Renal Ultrasound may be used to grade and monitor progress of chronic kidney disease.